“New Avenues for Listening.” Sensory Culture in the Digital Age and the Persistence of Utopia - Violeta Nigro Giunta; Nicolò Palazzetti (Transposition)
Michael Bull is a Professor of Sound Studies at the University of Sussex, in England. His research focuses on the relationship between new mobile technologies and auditory culture in everyday life, at the crossroads of urban studies, media studies and sound studies. In this interview, he talks about his background in sociology and philosophy, his research on personal stereos, his theoretical references (from Simmel to Adorno), and his views on the future developments of studies on sound culture, senses, and society.